Pernikahan di Kalangan Ikhwan dan Akhwat Pada Lembaga Wahdah Isalamiyah Kendari - Wa Ode Winesty Sofyani; La Ode Aspin (Laboratorium Jurusan Antropologi, Fakultas Ilmu Budaya, Universitas Halu Oleo, 2014)
This study aims to determine and to describe how the processes and functions of marriage among men and women in institution of Wahdah Islamiyah Kendari. Data collected through observation, in-depth interviews, and data analysis. The results showed that marriage performed by Wahdah Islamiyah Kendari based on Sayriat Islam. There are several stages or wedding process conducted by Wahdah Islamiyah, first, the man who wants to get married reports to his supervisor, then his supervisor conveys to the LP2KS. Then, the LP2KS will hold ta'ruf or proposal for desired women as an introductory phase that had previously been done coaching. The next step is nadzar, as a stage to know more detail as being allowed to see the prospective partner. Next, there is an agreement of both parties to proceed to the next level. The man who is accompanied by LP2KS will come to the woman’s house to propose. In this proposal will result an agreement of both parties to prepare for marriage. The series of wedding ceremony are offer and acceptance (ijab qabul) marriage sermon delivery, wedding announcements, wedding advice, and the last is wedding party (walimah). Keywords: marriage, islam